Designing Lexicogrammar Microlearning-Based Materials Infused With Listening Skills For 7th Graders - Mardiana, Rizdika; Darmahusni, Darmahusni; Astuti, Dwi; Aziz Muslim, Muhamad (International Journal of Educational Research & Social Sciences, 2023)
This study focused on the designing of English lexicogrammar materials that incorporate microlearning for junior high school students, especially 7th graders. The study aimed to develop effective instructional materials that enhance students' understanding of lexico-grammatical concepts through microlearning. A design-based research methodology was employed in this study in three phases (Richey & Klein, 2014b), namely analysis, design, and development. Information related to existing materials was gathered; the product model was planned; and the prototype design was then developed. Data was existing learning materials collected from teachers after they were interviewed and filled out a questionnaire. This study also utilized qualitative content analysis to examine a set of existing learning materials consisting of textbooks, PDFs, and ppt slides. The findings showed that the existing materials are not microlearning-based. The design of learning materials in lexicogrammar integrated with the listening skill named medium of microlearning objects was in the form of two podcasts, one audiobook, and some interactive games in integration with listening skill.